PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBAHASA INGGRIS BERDASARKAN TEORI KECERDASAN MAJEMUK (MULTIPLE INTELLIGENCES) PADA MATERI BALOK DAN KUBUS UNTUK KELAS VIII SMP - Wicaksono, Dian Panji; Kusmayadi, Tri Atmojo; Usodo, Budi (Jurnal Pembelajaran Matematika, 2014)
Abstract : This research aimed to produce and describe the process and the result of the development of Mathematics learning set in English, based on the multiple intelligences theory on topic of cuboid and cube. This research was conducted in seventh grade of SMPN 1 Ngadirojo, SMP N 3 Ngadirojo, and SMPN 2 Ngadirojo that each of those has 32 students. This research was developmental study, i.e. the development of learning set based on the multiple intelligences theory as mentioned above. The development model thatâs used refers to the Tjeerd Plomp one. Based on the conducted research, there were some conclusions as the followings (1) The process of the development of Mathematics learning set in English, based on the multiple intelligence theory: (a) The initial investigation phase obtained supporting theories for learning set development such as multiple intelligence theory by Gardner, Armstrong, and Bellanca, 2013 curriculum investigation that mandates to involve the multiple intelligences in Mathematics learning, studentsâ condition investigation that have various dominant intelligent. (b) The design phase obtained the developed learning set, i.e. lesson plan, student text book, student work sheet, and assessment sheet arranged in English, research instrument plan that consists of learning equipment validation sheet, observation sheet of learning implementation, observation sheet of studentsâ multiple intelligences involvement activity, and studentsâ response questionnaire. (c) On the realization phase, itâs arranged the learning set and research instrument. (d) On the test, evaluation, and revision phase, the learning set and limited trial were validated. (2) The result of development of Mathematics learning set in English, based on multiple intelligences theory: (a) The validity of learning set on lesson plan was 3.96, student text book 3.72, student work sheet 4.02, and assessment sheet 3.86. (b) The developed learning set could be used with a little revision and the average of learning implementation was 4.22. (c) This developed learning set could be said that it has been effective because the studentsâ multiple intelligences involvement activity reached 89,46% and the studentsâ responses were positive. Although the classical thoroughness was not achieved because only 35.42% of students met the minimal achievement criteria.Keywords : Mathematics Learning Set in English Based, MultipleÂ  Intelligences, cube andÂ  cuboid.Â  Â  Â Â